THE ROLE OF GENDER IN MODERATING SPENDING HABITS AND FINANCIAL LITERACY ON PURCHASING DECISIONS - Kristika, Intan Dharma; Hermawan, Sigit; Amalia, Nadhifah Hikma Adi; Shofiya, Lailatus (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: The purpose of this study was to determine how Spending Habits and Financial Literacy affect Multi Level Marketing purchases on Gender. Method: This Quantitative research uses the subject members of PT Gemilang Citrus Berjaya. The sampling technique used was purposive sampling and obtained 133 subjects. The data collection technique uses a Likert scale arranged based on items derived from aspects and indicators of each variable. The data analysis technique used uses PLS4 software. Results: The results show that the significance value is greater than 0.05, which means that there is no relationship between spending habits and purchasing decisions, gender in moderating Financial Literacy, and gender in moderating Spending Habits. The significant value is smaller than 0.05, which means that Financial Literacy affects purchasing decisions. Novelty: This study provides insights into the role of gender as a moderating variable in the relationship between Spending Habits, Financial Literacy, and purchasing decisions in the Multi Level Marketing context.